INFLUENCE OF ANTHROPOGENIC FACTORS ON RIVERS OF THE WESTERN REGION OF THE UKRAINIAN CARPATHIANS - Snitynskyi В.; Khirivskyi П.; Zelisko О.; Ivankiv М.; Hnativ І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Anthropogenic burden on water bodies is constantly increasing due to population growth and urbanization processes characterizing our time. A significant human impact on water bodies is an objective circumstance, because today, technology is the basis of the world economy and uses a lot of water, and discharges after production are very polluted. Heavy pollution of aquatic ecosystems with nutrients and runoff of agricultural land has led to the eutrophication of not only lakes and reservoirs, but also many watercourses. Significant factors of anthropogenic eutrophication of water bodies include reduction of water exchange, formation of stagnant zones, construction of dams and thermal pollution of water. The aim of the work is to assess the impact of urbanization of the Western region of the Ukrainian Carpathians on the ecological condition of rivers and natural self-cleaning processes. Assessment of the impact of urbanization of the Western region of the Ukrainian Carpathians on the ecological status of rivers showed unsatisfactory hydrochemical parameters of some small rivers in the region. The study confirms an excess of the standard values of the indicators of total iron (2.4 times) manganese (5 times) and suspended solids – 1.53 times for fishery waters. Anthropogenic activities related with agricultural production, water and forestry activities, plowing and deforestation lead to a significant change in the conditions of river runoff formation. In particular, the main volumes of river water pollution are caused by insufficient treatment of sewage at treatment facilities, rainwater from the territory of industrial areas that are not treated, wash away from water catchments of fertilizers and pesticides introduced into the soil, unauthorized dumps of household waste in riverbeds, and unauthorized mining developments that worsen the hydrological regime and the processes of natural water purification.